2019
DOI: 10.3390/cancers11101444
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid 18F-FDG-PET/MRI Measurement of Standardized Uptake Value Coupled with Yin Yang 1 Signature in Metastatic Breast Cancer. A Preliminary Study

Abstract: Purpose: Detection of breast cancer (BC) metastasis at the early stage is important for the assessment of BC progression status. Image analysis represents a valuable tool for the management of oncological patients. Our preliminary study combined imaging parameters from hybrid 18F-FDG-PET/MRI and the expression level of the transcriptional factor Yin Yang 1 (YY1) for the detection of early metastases. Methods: The study enrolled suspected n = 217 BC patients that underwent 18F-FDG-PET/MRI scans. The analysis re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 52 publications
1
21
0
Order By: Relevance
“…The majority of radiogenomic literature on breast cancer [34] relies almost exclusively on DCE-MRI (dynamic contrast-enhanced MRI) imaging features and, in some cases, on positron emission tomography/magnetic resonance (PET/MR) imaging [35,36]. Ten TCGA-TCIA-based studies were included in our review, and most of them aimed to capture associations between imaging features and breast cancer intrinsic molecular subtypes.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of radiogenomic literature on breast cancer [34] relies almost exclusively on DCE-MRI (dynamic contrast-enhanced MRI) imaging features and, in some cases, on positron emission tomography/magnetic resonance (PET/MR) imaging [35,36]. Ten TCGA-TCIA-based studies were included in our review, and most of them aimed to capture associations between imaging features and breast cancer intrinsic molecular subtypes.…”
Section: Resultsmentioning
confidence: 99%
“…A closely related field is 'radiogenomics', which explores the associations between imaging phenotype (radiomic data) and disease genotype (genomic patterns) [13,14]. Two public data resources such as The Cancer Genome Atlas (TCGA) and The Cancer Imaging Archive (TCIA), provide cancer genomic profiling and medical images counterpart, respectively [15,16], to promote cross-disciplinary research including radiogenomic studies [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 shows a summary of the topics and the papers included for each topic [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. The majority of papers are focused on prostate cancer (PCa) and radiomics.…”
mentioning
confidence: 99%
“…In the last years, a large amount of data has been published, such as in the current issue of Cancers , in order to apply this in diverse settings of disease. Castaldo et al [ 30 ] and Schiano et al [ 32 ] evaluated the role of radiomics in breast cancer. The first group of authors concluded the ability of radiomic features by MRI to discriminate major breast cancer molecular subtypes, thus potentially guiding a personalized treatment [ 30 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation